IMPROVING STUDENTS' SPEAKING SKILL THROUGH DEBATE - Indra Kurniawan Siregar; Rica Umrina Lubis (Journal of English Education and Linguistics, 2021)
Speaking is one of the important skills in language learning. Speaking is the act, utterance or discourse of one who speaks. It also can be defined as an activity in giving and asking information as if dialoguing by two or more people. In speaking, there is a process of communication between speaker and listener. People put ideas into words, talking about perceptions and feeling they want other people to understand. The writer observed that most students are difficult to put ideas into word through communication in speaking English. To solve the problem, the writer conducted classroom action research, by implementing debate. The writer applied two cycles in this research. Each cycle consist of three meetings. The participant of this study was one class consists of 32 students. The instrument for collecting the data was speaking test, observation sheet and document. Based on the research result, showed the progressive mean of the students. The first meeting was 46,87, second meeting was 50,09, third meeting was 60,28, the fourth meeting was 65,12, the fifth meeting was 73,56 and the sixth meeting was 77,81. So, the mean in the second cycle was higher than the first cycle.It is indicated that the application of debate technique improve students’ speaking skill.